Quail growth curve model identity (Research, Society and Development, 2020)
In this study, we sought to apply the model identity technique to compare the influence of eight treatments on growth parameters for three broiler quail lines, estimated using a logistic nonlinear regression model. For the analysis, we used the weight and age data obtained for three lines of European broiler quails (Coturnix coturnix coturnix) in a completely randomized 2×4 factorial scheme, with two levels of metabolizable energy (2900 and 3100 kcal of ME kg-1 of diet), four levels of raw protein (22%, 24%, 26% and 28% crude protein), and six repetitions. Results obtained for model identity tests indicated that although there were no significant differences among the parameters of the model between the treatments evaluated in each strain, there were, with the exception of Treatment 5 (3100 kcal of ME kg-1 and 22% crude protein), significant differences with respect to the adult weight parameter between lines within each treatment.